THE USE OF LITERATURE IN DEVELOPING STUDENTS’ CHARACTERS THROUGH AUTHENTIC ASSESSMENT - Wiandari, Fadhillah; Pratiwi, Siti Habsari (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
Students’ character can be developed in the learning process. Literature at schools in Indonesia is always considered complimentary and unimportant, even though literature is very influential in developing students’ skill in language. Literature is an important source that can influence the development of students’ character. This paper argues that the authentic assessment of the literary sources being taughtat schools helpsteachers to deal with ways of developingstudents’ character. Thus, this paper is to demonstrate the authentic assessment of literary sources taught atthe third grade of elementary schools at MIN 2 Aceh Tamiang in developing students’ character. The study used a mixed method; the use of experimental and qualitative methods. Experimental method was used to assess cognitive domains while qualitative descriptive was used to show affective and psychomotor domains. The findings show that in the cognitive domain, the assessment of poetry and drama are best carried through written, oral, and assignment tests. The affective domain is best performed through observation and journals while the psychomotor domain is done effectively through portfolios and performance appraisals. The paper shows that the literature teaching through authentic assessment at schools develops students’ responsibility, hard work, creativity, friendliness, and discipline. The finding also reveals that the scores obtained by students have reached the minimum scores of passing after the use of authentic assessment.